Analysis of the impact of selected financial ratios and macroeconomic factors on share price: Empirical evidence from selected emerging ASEAN countries mining and oil sector - Dela Cruz, Marielle C. (Animo Repository, 2022)
This paper analyzes the impact of selected financial ratios and macroeconomic factors on the share price of listed companies in the mining and oil sector of Indonesia Stock Exchange, Philippine Stock Exchange, Stock Exchange of Thailand and Hanoi Stock Exchange. The objectives of the study were as follows: First, to determine which financial ratios have an impact on the share price. Second, to determine which macroeconomic factors have an impact on the share price. To answer the study’s research questions, the researchers collected financial data from 28 listed companies in the Indonesia Stock Exchange, 11 listed companies in the Philippine Stock Exchange, 11 listed companies in the Stock Exchange of Thailand and 11 listed companies in the Hanoi Stock Exchange. While the macroeconomic factors were gathered from the central banks of the respective countries. A panel data regression analysis was performed on the data. The results of the study were the following: Return on assets, interest rate and world oil price showed a significant impact on the share price of listed Indonesian mining and oil companies. In the context of the Philippines, interest rate, inflation rate and world oil price were shown to have a significant impact on the share price. While in the listed Thai mining and oil companies, only the interest rate showed a significant impact on the share price. Lastly, current ratio, GDP and world oil price showed a significant impact on the share price of listed Vietnamese mining and oil companies.